2022
DOI: 10.1136/heartjnl-2021-320684
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-related cardiovascular conditions and outcomes in a United States Medicaid population

Abstract: ObjectiveThis study aims to examine the incidence of pregnancy-related cardiometabolic conditions and severe cardiovascular outcomes, and their relationship in US Medicaid-funded women.MethodsMedicaid is a government-sponsored health insurance programme for low-income families in the USA. We report the incidence of pregnancy-related cardiometabolic conditions (hypertensive disorders and diabetes in, or complicated by, pregnancy) and severe cardiovascular outcomes (myocardial infarction, stroke, acute heart fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…29 The risk can also be immediate in women with HDP, with an about twofold increase in severe cardiovascular outcomes, such as myocardial infarction and stroke, from pregnancy through to 60 days after birth. 31 Heart failure with preserved ejection fraction (HFpEF) 32 is an emerging global health problem with a female predominance and often associated with hypertension. 33 A retrospective cohort study using the New York and Florida Inpatient Databases (2006-2014) found a twofold increased risk of HFpEF hospitalisation among women with a history of preeclampsia or eclampsia.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…29 The risk can also be immediate in women with HDP, with an about twofold increase in severe cardiovascular outcomes, such as myocardial infarction and stroke, from pregnancy through to 60 days after birth. 31 Heart failure with preserved ejection fraction (HFpEF) 32 is an emerging global health problem with a female predominance and often associated with hypertension. 33 A retrospective cohort study using the New York and Florida Inpatient Databases (2006-2014) found a twofold increased risk of HFpEF hospitalisation among women with a history of preeclampsia or eclampsia.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…For women with preeclampsia, coronary heart disease, heart failure and stroke were substantially higher in the first one to ten years after an affected pregnancy 29 . The risk can also be immediate in women with HDP, with an about twofold increase in severe cardiovascular outcomes, such as myocardial infarction and stroke, from pregnancy through to 60 days after birth 31 …”
Section: Hypertensive Disorders Of Pregnancymentioning
confidence: 99%
“…In addition to pre-existing heart disease, gestational hypertension and diabetes, as well as pre-eclampsia and eclampsia, are associated with an increased risk of adverse cardiovascular outcomes both in the short and long-term. In this issue of Heart , Marschner and colleagues1 report an incidence of cardiometabolic conditions (hypertensive disease and diabetes) of 224.3 (95% CI 221.3 to 227.3) per 1000 births among 74 510 women, mean age 26.4 years (SD 5.5) in a cross-sectional study of Medicare patients from 2015 to 19. The incidence of adverse cardiovascular outcomes (myocardial infarction, stroke, acute heart failure, cardiomyopathy, cardiac arrest, ventricular fibrillation, ventricular tachycardia, aortic dissection/aneurysm and peripheral vascular disease) was 10.8 (95% CI 10.1 to 11.6)per 1000 births.…”
mentioning
confidence: 99%
“…However, one striking difference between the USA and similarly wealthy countries, which may contribute to rising maternal mortality, is its fragmented insurance coverage. Marschner et al give readers a revealing snapshot of the intersection between cardiovascular maternal health and insurance coverage in an important and unique US demographic, pregnant women covered under Medicaid 8. As the US public insurance programme aimed to improve access to basic healthcare for those otherwise cannot afford it, Medicaid plays a pivotal role in supporting pregnant women living in poverty and currently provides coverage for half of all US births 9…”
mentioning
confidence: 99%
“…The reasons for this are likely multifactorial, including unconscious provider bias, and the study acknowledged limitations in ethnicity data collection and therefore direct examination of racial disparities within the Medicaid population. However, a disproportionate lack of access to care as a driving factor may be extrapolated when taking the study’s mention that the Medicaid population ‘skews non-White, with 65% of Black women being covered by Medicaid.’8…”
mentioning
confidence: 99%